PEMANFAATAN TUMPI (KULIT ARI JAGUNG) TERAMONIASI SEBAGAI PAKAN DALAM UPAYAREVITALISASI USAHA TERNAK POTONG - Baginda Iskandar Moeda Tampoebolon (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2002)
The purpose of the experiment was to clarify the qualitiy of amonia-teatrnent Corn Husk by examining dry matter (DM) and organic matter (OM) digestibilities, and volatile fatry acids (VFA) and ammonia (NH) productions. Five levels of urea namely, U0 =0%,U2=2%, U,=4%,U0=6% and U8=8% were used for ammonia-treatment process with the three weeks incubation. Each treatment containg three replications. Dry matter and organic matter digestibilities, and VFA and NHJ production were analyzed according to the method of Tilley and Terry (1963). The result showed that ammonia-treatment significanly increased DM and OM digestibilities, and VFA and NHJ production were produced by level of 6% urea.